FILSAFAT IDEALISME DAN ANALISIS IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH PENGGERAK SEKOLAH DASAR DI SDN 216/III SUNGAI LANGKAP - Elza Eka Lestari; Desyandri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
This study aims to discuss "Analysis of the Implementation of the Independent Curriculum in the Mobilizing Schools of SDN 216/III Sungai Langkap. This type of research is qualitative, the approach used is a phenomenological approach, which is based on the explanation of this phenomenological approachthe experiences experienced by key informants.The location of this research was carried out at SDN 216/III Sungai Langkap where the key informants were teachers, principals and supervisors. In this study the data collection techniques used were observation, interviews, and documentation studies. In order for the data to be tested for validity, the following precautions are taken: (a) extending the data collection period, (b) observing until the data can be said to be saturated, (c) conducting triangulation, and (d) involving colleagues for discussion. From the results of research conducted by researchers, the results of the research are that the independent curriculum is a reference for driving schools, where the purpose of this independent curriculum is to produce students with a Pancasila student profile, which is what is meant by a profilePancasila students are students who have noble character, are independent, reason critically, are creative, work together, have a sense of diversity. driving school principals encourage a variety of participatory, unique, and many innovative programs. Fostering cooperation with teachers who support their leaders to participate in realizing driving schools